Advances in Web-Based Learning - ICWL 2023 22nd International Conference, ICWL 2023, Sydney, NSW, Australia, November 26-28, 2023, Proceedings - Xie, Haoran; Lai, Chiu-Lin.; Chen, Wei.; Xu, Guandong; Popescu, Elvira (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book constitutes the proceedings of the International Conference on Web-Based Learning, ICWL 2023, in Sydney, NSW, Australia, in November 2023. The 9 full papers together with 7 short papers included in this volume were carefully reviewed and selected from 23 submissions. The conference focuses on subjects such as Semantic Web for E-Learning, through Learning Analytics, Computer-Supported Collaborative Learning, Assessment, Pedagogical Issues, E-learning Platforms, and Tools, to Mobile Learning.
Massive Open Online Courses and Learning Analytics -- Online Learning Environment with Tools -- Learning Content Management -- Computer Support for Intelligent Tutoring.
Keywords: Education -- Data processing; Computers and Education